Collision avoidance for unmanned surface vehicle in busy waterways based on improved DDPG and IMMKF - Te Lian; Qijun Liu; Defeng Wu; Yuqin Li; Chunxin Tian (Ocean Engineering, 2026)

Corrigendum to “Linking microbial functional partitioning with methane productivity and stability in microbial electrolysis cell–anaerobic digestion hybrid systems” [Bioresour. Technol. 453 (2026) 134629] - Xue-Ting Wang; Yanxue Li; Yuxin Pan; Xue Xing; Bo Wang; Defeng Xing; Jun Nan; Jonathan Tian En Lee; Eakalak Khan; Daniel C.W. Tsang; Nan-Qi Ren; Yong Sik Ok (Bioresource Technology, 2026)

Linking microbial functional partitioning with methane productivity and stability in microbial electrolysis cell–anaerobic digestion hybrid systems - Xue-Ting Wang; Yanxue Li; Yuxin Pan; Xue Xing; Bo Wang; Defeng Xing; Jun Nan; Jonathan Tian En Lee; Eakalak Khan; Daniel C.W. Tsang; Nan-Qi Ren; Yong Sik Ok (Bioresource Technology, 2026)

Performance evaluation of building-integrated photovoltaic windows with triple-glazing: Summer assessment in cold climate - Chunwen Xu; Xintao Tian; Rumei Yang; Shasha Song; Fei Han; Defeng Kong; Yelin Zhang (Energy and Buildings, 2026)

Altered functional connectivity within and between resting-state networks in ulcerative colitis - Yanjun Ren; Kaizhong Xue; Huijuan Xu; Lijie Hao; Quchuan Zhao; Tianyu Chi; Hongwei Yang; Xiaojing Zhao; Defeng Tian; Huihong Zhai; Jie Lu (Brain Imaging and Behavior, 2025)

Applying machine learning and genetic algorithms accelerated for optimizing ethanol production - Xu Yang; Nianhua Chen; Hui Yu; Xinyue Liu; Yujie Feng; Defeng Xing; Yushi Tian (Science of The Total Environment, 2024)

Efficient removal of hexavalent chromium from wastewater using a novel sodium alginate-biochar composite adsorbent - Yushi Tian; Xiaolin Sun; Nianhua Chen; Xintong Cui; Hui Yu; Yujie Feng; Defeng Xing; Weihua He (Journal of Water Process Engineering, 2024)

Description and genomic characterization of Streptococcus symci sp. nov., isolated from a child’s oropharynx - He Qi; Defeng Liu; Yang Zou; Nan Wang; Han Tian; Chunling Xiao (Antonie van Leeuwenhoek, 2021)
Using the culturomics approach, we isolated a new Streptococcus species, strain C17 T , from the oropharynx mucosa sample of a healthy 5-year-old child living in Shenyang, China. We studied the phenotypic, phylogenetic, and genomic characteristics of strain C17 T , which was identified as a Gram-positive, coccus-shaped, non-motile, aerobic, catalase-negative bacteria. Its growth temperatures ranged from 20 to 42 °C, with optimal growth at 37 °C. Acid production could be inhibited by two sugars, trehalose and raffinose. In C17 T , the reactions for enzyme lipase (C14) were confirmed to be negative, whereas those for alkaline phosphatase, α-glucosidase, and hippuric acid hydrolysis were positive. The C17 T genome contained 2,189,419 base pairs (bp), with an average G+C content of 39.95%, encoding 2092 genes in total. The 16S ribosomal RNA sequence showed 99.8% similarity with the newly identified Streptococcus pseudopneumoniae ATCC BAA-960 T . The main fatty acid components in C17 T were C16:0, C18:1 w7c, C18:0, and C18:1 w9c, all of which can be found in other species of the Streptococcus genus. Strain C17 T showed high susceptibility to clindamycin, linezolid, vancomycin, chloramphenicol, and cefepime, and moderate susceptibility to erythromycin. The obtained dDDH value between strain C17 T and the closest species was 52.9%. In addition, the whole genome sequence of strain C17 T had an 82.21–93.40% average nucleotide identity (ANI) with those strains of closely related Streptococcus species, indicating that the strain C17 T was unique among all Streptococcus species. Based on these characteristics, we determine that C17 T is a novel species, named Streptococcus symci sp. nov. (= GDMCC 1.1633 = JCM 33582).

Effects of sludge lysate for Cr(VI) bioreduction and analysis of bioaugmentation mechanism of sludge humic acid - Hongling Chen; Ruofei Jin; Guangfei Liu; Tian Tian; Chen Gu; Jiti Zhou; Defeng Xing (Environmental Science and Pollution Research, 2019)

Ecosystem carbon stock across a chronosequence of spruce plantations established on cutovers of a high-elevation region - Xueyong Pang; Junsheng Huang; Qingxia Zhao; Defeng Feng; Weikai Bao; Guanglong Tian (Journal of Soils and Sediments, 2017)

The structural characteristics, age of origin, and tectonic attribute of the Erguna Fault, NE China - Han Zheng; XiaoMeng Sun; DeFeng Zhu; JingXiong Tian; Song He; YingDe Wang; XuQing Zhang (Science China Earth Sciences, 2015)